HUBUNGAN BEBERAPA FAKTOR PASANGAN USIA SUBUR (PUS) DENGAN UNMET NEED KELUARGA BERENCANA (KB) DI DESA PENUNGKULAN KECAMATAN GEBANG KABUPATEN PURWOREJO TAHUN 2016 - Sullikhah, Sullikhah; Nugroho, Djoko; Dharmawan, Yudhy (Fakultas Kesehatan Masyarakat, 2017)
Unmet need is EFA which wishes to limit birth or delay pregnancy for the next two years but not using contraception. Unmet need in Penungkulan village, Gebang subdistrict, Purworejo Regency in 2016 is still quitehigh at 13,6%. The figure is still very far from the national target of 5%. The purpose of this study is to analyze the relationship of several factors EFA with unmet need KB. The type of research is explanatory research with cross sectional study design. The population of this study is 501 EFA in Penungkulan village. The sampling technique using simple random sampling with the number of samples of research as many as 81 EFA. Data were collected by using questioner and analyzed by univariate and bivariate with chi-square test and continuity correction method. The results of the study showed that there were no significant correlation with unmet need for family planning, ie EFA education (wife p-value = 0,481 , husband p-value = 0,965), knowledge (p-value = 0,941 ), health service affordability (p-value = 0,625 ), health officer support (p-value = 1,000 ). There needs to be an increase in IEC of family planning to EFA, and for EFAs who are afraid to use contraceptive for fear of adverse effects are advised to use other contraceptive according to EFAs condition.